Impact of Starch from Cassava Peel on Biogas Produced through the Anaerobic Digestion Process - Alla Mohammed Alrefai; Raid Alrefai; Khaled Younis Benyounis; Joseph Stokes (Energies, 2020)
Cassava is a form of food that is rich in starch abundant in many countries. Several bio-products can be extracted from its starch and used as an alternative for oil-based products. This study primarily aims to investigate the influence of the starch isolated from cassava peel on the quantity and quality of the biogas produced via anaerobic digestion. Beating pre-treatment was applied for the first time to isolate the starch and mechanically pre-treat the substrate. The influence of temperature, volatile solid and sludge quantity investigations were analysed with the aid of Design of Experiments (DOE). An optimisation process was applied in calculating the energy balance at the optimal results and this was needed in evaluating the impact of the starch on the biogas produced. The study revealed that the influence of the starch on the biogas quality is quite low and, as such, negligible. The largest biogas volume as obtained was 3830 cc at 37 °C, 4.2 g-VS and 50% sludge quantity, while at the same time the maximum CH4 g−1-VS was 850 cc g−1-VS at 37 °C, 1.1 g-VS and 50% sludge quantity. The optimal results show the energy gain could be achieved based on the set criteria.